UNDERSTANDING PLEONASMS IN SPEECH AND WRITING - Верховцова, Ольга (SWorldJournal, 2025)
Language is not only a means of communication, but also a rich, lively and multifaceted communication tool that allows people to convey the most subtle shades of thoughts, emotions, moods and feelings. In this context, stylistic techniques that enrich spe